The great transforming power: Music, poetry and friendship in Antonio Carlos Santos - Wolff, Joca (2020)
This is a text dedicated to Antonio Carlos Santos concerning his poetic, musical and intelectual journey from Rio de Janeiro to Florianópolis and then to Frankfurt as a three-way road. It relates to music, poetry and friendship and vice versa. For that it turns memory into story and looks at poetry as sound and sense down there in my friend’s house.